The True North Urgency of the Earth in Determining the Direction of the Qibla According to Fiqh and Falak Science - Asmuni Asmuni; Hasan Matsum; Imamul Muttaqin (Budapest International Research and Critics University, 2020)
True North true north is any point on the earth to the North pole, this is because the North and South poles point precisely to the earth's axis of rotation. Therefore true north is North based on the earth's axis not North based on the earth's magnetism. So the difference is true North shows the true north direction of the earth while magnetic North is the North direction of the magnetic compass needle. Magnetic north does not coincide with Earth's true north. To find out the true North of the earth using a compass, you need to know the magnetic declination first. To know the magnetic declination can be done through a magnetic declination calculator such as WMM (world magnetic model) which can be downloaded through the crowdmag application playstore. In determining the direction of the Qibla it is required to determine the True North point of the earth.